Health Impact Assessment of Covid-19 Towards Maternal Health Care in West Jakarta - Fitrianingrum, Nisaatul Maharanita; Sabarinah, Sabarinah; Pratomo, Hadi (Journal of Maternal and Child Health, 2021)
Background: The Large-Scale Social Restrict